Qualitative welfare risks of cows offered to a Dutch mobile slaughter unit - Ursinus, Winanda W.; Voogt, Annika M.; Bongers, Johan H.; Sijm, Dick T. H. M. (Frontiers in Animal Science, 2023)
In the Netherlands, a pilot had started for a Mobile Slaughter Unit (MSU) for the killing of cull dairy cattle not fit for transport, but suitable for slaughter to save valuable meat. The Office for Risk assessment & Research (BuRO), was asked to assess the risks for animal welfare. As a thorough risk assessment would be very time consuming a qualitative framework was used instead. The goal of the current study is to qualitatively describe the relevant risks involved for cow welfare when using an MSU compared to current practice, by applying a rapid comparative risk assessment of animal welfare. The assessment framework consists of the following steps: Identification and description of scenarios, and assessing and comparing the most relevant animal welfare risks in the scenarios, including hazard identification, hazard characterization, exposure, and risk characterization on animal welfare. Two main scenarios were identified, one with and one without an MSU. The second scenario was split into three sub-scenarios: killing on-farm/in housing unit, emergency slaughter, and conventional transport to the slaughterhouse. The most relevant risks associated with operating an MSU were: leaving the cow alive on-farm when not fit for slaughter, forcing the cow to walk to and into the MSU (however, this risk is likely higher in conventional transport of unfit cows), and insufficient stunning and bleeding leading to questionable unconsciousness (however, this risk is likely higher in an emergency slaughter). The MSU is a means to prevent exacerbation of deterioration of welfare of cows that are unfit for transport, but fit for slaughter, and, it reduces exposure to stressors (hazards) conventionally present during transport and at a stationary slaughterhouse. The rapid comparative risk assessment of animal welfare supported swift decision making: the national competent authority (i.e. NVWA in the Netherlands) and policy makers could improve and develop risk mitigating actions as well as decide on allowing the use of an MSU. Mobile slaughter facilities can reduce welfare risks of cull dairy cows unfit for transport but fit for slaughter when appropriately designed and used, and with sufficient supervision.